2023
DOI: 10.3390/ijms24065166
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Mesenchymal-Derived Extracellular Vesicles and Their Role in the Prevention of Persistent Post-Breeding Induced Endometritis

Abstract: Persistent post-breeding induced endometritis (PPBIE) is considered a major cause of subfertility in mares. It consists of persistent or delayed uterine inflammation in susceptible mares. There are many options for the treatment of PPBIE, but in this study, a novel approach aimed at preventing the onset of PPBIE was investigated. Stallion semen was supplemented with extracellular vesicles derived from amniotic mesenchymal stromal cells (AMSC-EVs) at the time of insemination to prevent or limit the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…To date, only one study has evaluated the in vivo effects of MSC-CM intrauterine infusion on mares that are susceptible to PPBIE [30], and another study showed that AMSC-conditioned medium (AMSC-CM) was effective in the replenishment of endometrial cells and uterine regeneration [31]. Lange-Consiglio and colleagues [32] demonstrated that the supplementation of AMSC-EVs to semen resulted in the successful modulation of post-insemination inflammatory responses in mares that could be able to prevent PPBIE.…”
mentioning
confidence: 99%
“…To date, only one study has evaluated the in vivo effects of MSC-CM intrauterine infusion on mares that are susceptible to PPBIE [30], and another study showed that AMSC-conditioned medium (AMSC-CM) was effective in the replenishment of endometrial cells and uterine regeneration [31]. Lange-Consiglio and colleagues [32] demonstrated that the supplementation of AMSC-EVs to semen resulted in the successful modulation of post-insemination inflammatory responses in mares that could be able to prevent PPBIE.…”
mentioning
confidence: 99%